FROM FANTASY TO REALITY: THE VISUALIZATION AND TRANSFORMATIVE THINKING OF THE CHARACTER BARBIE IN ITS MOVIE VERSION - Isna Mufidah; Wiwiek Afifah (UIN Raden Mas Said Surakarta, 2025)
The representation of women’s identities in the media has undergone significant shifts amidst the dynamics of contemporary popular culture. The film Barbie (2023) presents a narrative that not only showcases symbols of femininity but also offers a reflective journey of a character questioning the meaning of her existence. This research aims to analyze the process of transformative thinking in Barbie’s character, based on Mezirow’s (1994) transformative thinking theory, as well as to examine the visual signs and symbols in the film through the semiotic approach of Barthes (1968). the data were collected through visual observation, transcription of reflective scenes, and documentation of narrative symbols. The data were then analyzed using a content analysis method. The results show that the character Barbie undergoes stages of transformative thinking from disorienting dilemma to transformation of perspective which are represented through the changes in body language, critical dialogue, and visual symbols, such as costumes and colours. This process not only reflects Barbie’s personal journey from doll to human but also voices a critique of gender social construct symbols, such as high heels, the colour pink, and Barbie’s interactions with other characters. These all emphasize the shift from the representation of women as passive to active and reflective subjects. Thus, the Barbie movie offers a new space for interpreting women’s identities and demonstrates the potential of popular media as a means of critical and transformative reflection.